The start-up period of styrene degrading biofilters - Weigner, P; Páca, J; Loskot, P; Koutský, B; Sobotka, M (Folia microbiologica, 2001)
Styrene vapors from contaminated air were eliminated using long-term adapted mixed microbial culture inoculated on four perlite packed biofilters (serial arrangement, up-flow configuration). During start-up the inlet concentration of styrene rose from 175 to 1300 mg/m3 of total carbon. The total actual residence time in the four biofilters was 24 s. Styrene was successfully degraded by the microbial population in the biofilter. An average of 66% of eliminated styrene was transformed to CO2. The removal efficiency of the pollutant was, after 18 d of start-up, nearly 85% at an organic load of 170 g/m3 per h. The concentration profiles along the bed height were linear for various pollutant inlet concentrations. The total amount of microorganisms in analyzed biomass from the biofilters was about 10(9) per gram of dry packing mass. The moisture content was around 80% in all biofilters.
Keywords: oxid uhličitý; látky znečišťující vzduch; styren; Carbon Dioxide; Air Pollutants; Styrene; Biodegradation, Environmental; biodegradace; půdní mikrobiologie; Soil Microbiology